Impact of the COVID-19 pandemic on number of deaths in Ghana: an application of ARIMA with intervention analysis - Hesse, Christian Akrong; Kpeglo, Emmanuel Dodzi; Boyetey, Dominic Buer; Nadarajah, Saralees (Frontiers in Public Health, 2025)
Over the past three years, the novel coronavirus (COVID-19) outbreak has caused millions of unexpected deaths worldwide. Ghana, like many other countries, recorded numerous COVID-19 deaths. The number of deaths from the commencement of the crisis formed a time series. This study examines the effect of the COVID-19 pandemic on the number of deaths in Ghana using intervention analysis on time series data. Initially, we generated an ARIMA (3, 1, 0) model to examine monthly death data in Ghana from January 2018 to December 2022, identifying March 2020 as the critical intervention point. March 2020 marked the commencement of the COVID-19 pandemic in Ghana. Secondly, we employed the ARIMA model to predict the post-pandemic death trend, and ultimately, we found no substantial discrepancy between the estimated and observed death count. Consequently, the analysis concluded that, despite a surge in global deaths, the estimated model indicated that the pandemic’s emergence did not result in a significant change in the number of deaths in Ghana beyond the anticipated figures based on pre-pandemic patterns.